Enhanced thallium(I) removal from wastewater utilizing biochar derived from high-potassium fruit peels - Canbin Zhong; Huanbin Huang; Huosheng Li; Ziyi Deng; Jianying Mo; Yuan Xie; Jianyou Long; Gaosheng Zhang; Tangfu Xiao; Mingxia Yu; Ziqing Xiao; Yirong Deng (Desalination and Water Treatment, 2025)
Biochar derived from fruit peels can effectively remove thallium (Tl) from wastewater, yet the specific role of potassium (K) in this process remains underexplored. This study focuses on K-rich biochars, particularly from banana peels, to elucidate the underlying mechanisms of Tl sequestration. The biochars were found to contain various K species, including loosely bound K in dissolvable compounds, exchangeable K cationic resin-like carbonaceous polymers, and tightly bound K in the biochar matrix. A positive correlation was observed between K release and Tl removal efficiency, indicating that ion exchange involving exchangeable K plays a dominant role in Tl uptake. Adsorption kinetics followed a pseudo-second-order model, while isotherms aligned with the Langmuir model, with a maximum adsorption capacity of 224 mg/g at pH 5.8. When applied to real acidic mine drainage containing 7.0 μg/L of Tl, the biochar reduced Tl concentrations to below 2.0 μg/L, thereby meeting local industrial discharge standards. Characterization techniques confirmed that Tl removal primarily occurred through K(I)-Tl(I) cationic exchange and chloride-mediated precipitation as insoluble thallium chloride. These findings not only highlight the efficacy of K-rich biochars for Tl remediation but also clarify the pivotal role of biochar-derived potassium in facilitating Tl removal from contaminated waters.